COMPARATIVE FUNCTIONAL ANALYSES OF ULTRABITHORAX REVEAL MULTIPLE STEPS AND PATHS TO DIVERSIFICATION OF LEGS IN THE ADAPTIVE RADIATION OF SEMI-AQUATIC INSECTS. (1st August 2014) - Khila, Abderrahman; Abouheif, Ehab; Rowe, Locke
Abstract: Invasion of new ecological habitats is often associated with lineage diversification, yet the genetic changes underlying invasions and radiations are poorly understood. Over 200 million years ago, the semi-aquatic insects invaded water surface from a common terrestrial ancestor and diversified to exploit a wide array of niches. Here, we uncover the changes in regulation and function of the gene Ultrabithorax associated with both the invasion of water surface and the subsequent diversification of the group. In the common ancestor of the semi-aquatic insects, a novel deployment of Ubx protein in the mid-legs increased their length, thereby enhancing their role in water surface walking. In derived lineages that specialize in rowing on the open water, additional changes in the timing of Ubx expression further elongated the mid-legs thereby facilitating their function as oars. In addition, Ubx protein function was selectively reversed to shorten specific rear-leg segments, thereby enabling their function as rudders. These changes in Ubx have generated distinct niche-specialized morphologies that account for the remarkable diversification of the semi-aquatic insects. Therefore, changes in the regulation and function of a key developmental gene may facilitate both the morphological change necessary to transition to novel habitats and fuel subsequent morphological diversification.